EMPOWERMENT OF THE MILITARY IN THE USE OF DRONE DEFENSE EQUIPMENT TO INCREASE READINESS FOR MILITARY OPERATIONS: Pemberdayaan Rindam Dalam Penggunaan Alutsista Drone Guna Meningkatkan Kesiapan Tugas Operasi Militer - Adv Bangun P. Hutajulu; Arief Prayitno; Chandra (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This Study Analyzes the Role of The Regional Military Command Training Regiment (Rindam) Jaya in The Utilization Of Drone Weapon Systems (Alutsista) To Enhance The Operational Readiness Of The Indonesian Army. With Technological Advancements, Drones Have Become Essential Components in Modern Defense Strategies, Enabling More Effective Surveillance and Strikes on The Battlefield. Rindam Jaya Is Responsible for Training Soldiers in Drone Operation, Maintenance, And Tactical Utilization, Ranging from Micro Uavs for Short-Range Surveillance to High-Altitude Long-Endurance (HALE) Uavs for Strategic National Missions. The Integration of Drones into Military Training Includes Realistic Battlefield Simulations, Preparing Soldiers for Quick Responses in Various Dynamic Scenarios. This Study Employs a Qualitative Approach, Collecting Data Through Interviews and Literature Related to Drone Technology and Military Training. The Findings Show That Rindam Plays a Impotant Role in Ensuring the Technical and Tactical Readiness of Soldiers; However, Challenges Include Limited Training Facilities and The Need for Collaboration With The Defense Industry to Develop Domestic Technology. The Study Concludes That Ongoing Adaptation to Technological Advancements and Comprehensive Training Program Enhancements Are Essential for Rindam to Support the Indonesian Army's Operational Readiness In Facing Future Threats. This Research Aims to Contribute to National Defense Policy and Strengthen Indonesia's Military Readiness.